Pengembangan Instrumen Tes untuk Mengukur Kemampuan Literasi Sains Siswa Kelas V Sekolah Dasar pada Materi Sistem Pencernaan Manusia - Kurnia Dewi (Jurnal Kualita Pendidikan, 2022)
This study aims to develop a test instrument based on scientific literacy on the material of the digestive system. The design of this research is Research and Development (R&D). The test instrument was tested for validity, reliability, and the level of difficulty and differentiating power of questions to determine students' scientific literacy abilities. The subjects of the research trial were fifth grade students of SD Negeri Tosaran, Kedungwuni District, Pekalongan Regency. The validity test was carried out with content validity, criteria, and expert validation. Reliability test is done by looking for the price of the reliability coefficient. The characteristic test is carried out by determining the level of difficulty and distinguishing power. The results of the reliability test obtained are the value of r in the 0.840 test. The results of the validity test showed that the instrument was declared to meet content validity, criteria, and expert validation with valid and very valid criteria. The characteristics of the evaluation instrument developed indicate that the instrument has a proportion of difficulty levels, namely 30% moderate questions, and 70% difficult questions. The results of the discriminatory analysis were then combined with the level of difficulty and obtained 10 items of good quality that could be used.